MANAJEMEN EKONOMI SEBAGAI SOLUSI PENATAAN KEHIDUPAN KELUARGA YANG LEBIH BAIK - Endah Widati; Zeinora Zeinora; Arief Sasmoko (Sosio e-Kons, 2016)
Established and fulfilled life is the desire of almost everyone. However, due to a variety of things, this desire can not be achieved. Big spending and uncontrolled and unbalanced by income makes a family experiencing economic difficulties, especially for people who have low and uncertain incomes. One solution to manage income and expenditure is to apply economic management family. Therefore, this study aims at determining how economic management family implementations can be a solution for a better life. The research uses qualitative descriptive method. The results showed that by applying economic management family, a family could plan carefully their wants and needsKeyword: Economic management family, Happy family